2023
DOI: 10.1111/luts.12490
|View full text |Cite
|
Sign up to set email alerts
|

Hygiene management of intermittent self‐catheterization using reusable silicone catheters in people with spinal cord lesions: A cross‐sectional Internet survey in Japan

Abstract: ObjectivesTo investigate hygiene management and catheter maintenance of reusable silicone catheters for intermittent self‐catheterization (ISC) in Japan and examine their relationship with symptomatic urinary tract infection (sUTI).MethodsWe conducted a cross‐sectional Internet survey of people performing ISC using reusable silicone catheters owing to spinal cord lesions in Japan. Hygiene management and catheter maintenance of reusable silicone catheters and the incidence and frequency of sUTI were evaluated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We have already reported findings on topic 1 3 and, subsequently, on the reusable silicone catheter part of topic 2. 7 Therefore, the present study reports findings on the SC part of topic 2. This study was conducted in accordance with the ethical standards of the Declaration of Helsinki and was approved by the ethical committee (the nonprofit organization MINS Research Ethics Committee; http://www.npomins.com/library/5fcf039bd6164603646daf12/602f7e0c12830e793 b214646.pdf).…”
Section: Methodsmentioning
confidence: 80%
See 4 more Smart Citations
“…We have already reported findings on topic 1 3 and, subsequently, on the reusable silicone catheter part of topic 2. 7 Therefore, the present study reports findings on the SC part of topic 2. This study was conducted in accordance with the ethical standards of the Declaration of Helsinki and was approved by the ethical committee (the nonprofit organization MINS Research Ethics Committee; http://www.npomins.com/library/5fcf039bd6164603646daf12/602f7e0c12830e793 b214646.pdf).…”
Section: Methodsmentioning
confidence: 80%
“…21 They highlighted that single-use HCCs improve QoL and were preferred over multiple catheter re-use among men and women practicing intermittent catheterization. 21 The limitations mentioned in our previous reports 3,7 still are relevant to this study: the inherent limitations of an internet survey, no national registration system for SCL in Japan, an exploratory study using data from the burden of illness study, use of self-reported sUTI, misremembering in responses, small sample size, and the dearth of information on the exact neurological level of SCL as well as urodynamic findings. Moreover, except manual dexterity, indoor movement, and bowel management, factors relevant to self-management were not investigated.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations